Zhodnocení ekonomických přínosů svazků obcí - Ficencová, Jana (Univerzita Pardubice, 2006)
Tato bakalářská práce se zabývá formami spolupráce měst a obcí v České republice se zaměřením na svazky obcí. Je shrnutím teoretických poznatků a pojmů dotýkajících se spolupráce obcí a dále obsahuje popis (analýzu) konkrétního svazku obcí (mikroregionu Černilovsko) se zaměřením na jeho projekty.

This bachelor work deals with forms of cooperation of towns and municipalities in The Czech Republic with its focus on associations of municipalities. It is a summary of theoretical knowledge and definitions related to the cooperation of municipalities and also includes description (analysis) of particular association (Černilovsko Microregion), which is focused on its projects.
Evaluation of associations of municipalities´ economical benefits
Keywords: cooperation of municipalities; microregions; Analysis; evaluation of projects; Spolupráce; Černilovsko; mikroregiony; analýzy; zhodnocení projektů